A novel customizable stent graft that contains a stretchable ePTFE with a laser‐welded nitinol stent. Issue 4 (3rd September 2018) - Chen, Yanfei; Tillman, Bryan; Go, Catherine; Cho, Sung Kwon; Clark, William W.; Hur, Tae Bong; Ding, Yicheng; Chun, Youngjae
Abstract: Customizable medical devices have recently attracted attentions both in dental and orthopedic device fields, which can tailor to the patients' anatomy to reduce the length of surgery time and to improve the clinical outcomes. However, development of the patient specific endovascular device still remains challenging due to the limitations in current 3D printing technology, specifically for the stent grafts. Therefore, our group has investigated the feasibility of a highly stretchable expanded‐polytetrafluoroethylene (ePTFE) tube as a customizable graft material with the laser‐welded nitinol backbone. In this study, a highly stretchable ePTFE tube was evaluated in terms of mechanical behaviors, in vitro biocompatibility of ePTFE with various stretchiness levels, and capability for the integration with the laser‐welded customizable nitinol stent backbone. A prototype stent graft for the swine's venous size was successfully constructed and tested in the porcine model. This study demonstrates the ability of ePTFE tube to customize the stent graft without any significant issue, for example, sweating through the stretched pores in the ePTFE tube, as well as in vivo feasibility of the device for bleeding control. This novel customizable stent graft would offer possibilities for a wide range of both current and next‐generation endovascular applications for the treatment in vascular injuries or diseases. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B: 911–923, 2019.